(untitled) (Research, Society and Development, 2022)
Pig farming and poultry farming stand out within agribusiness, however, they end up collaborating for the generation of waste. The objective of this work was to determine the maximum technical efficiency dose of the compost produced from the mixture of different organic residues in black oat pasture with different splitting of applications. The treatments were: mineral fertilization; without fertilization; organic fertilization at doses (5, 10, 15, 20, 25 and 30 Mg ha-1). The doses were divided into once and twice. Green matter (GM) and dry matter (DM) were evaluated at 45 and 75 days after emergence, in which the maximum technical efficiency dose (DMET) was obtained for each cutting period. Organic compost at doses of 10 to 30 Mg ha-1 for GM and 15 and 20 Mg ha-1 for DM was superior to mineral fertilization, regardless of splitting or not. The dose of 25 Mg ha-1 for DM was superior in a single application. DMET was found at doses of 19.1 and 18.7 Mg ha-1, in a single application of the organic compound, to obtain a yield of 23.9 and 3.0 Mg ha-1 of GM and DM accumulated, respectively. When splitting in two installments, the maximum production of accumulated GM (25.9 Mg ha-1) was obtained at the DMET of 22.9 Mg ha-1. As for DM, the maximum accumulated production (3.0 Mg ha-1) was from the DMET of 22.7 Mg ha-1, respectively.